KOEFISIEN DISTRIBUSI KENDARAAN UNTUK PERANCANGAN TEBAL PERKERASAN LENTUR DI MATARAM, BANDUNG, DAN SURABAYA - Suryo Putranto, Leksmono; Shinta Eka Setyarini, Ni Luh Putu (Jurnal Transportasi, 2010)
A comprehensive knowledge regarding vehicle distribution can be utilized to adjust vehicle distribution coefficient (C) on the Manual of Indonesian Flexible Pavement Design (SKBI-2.3.26.1987). This paper discusses the effect of city characteristics, lane configuration, and flow level on vehicle distribution in urban road lanes. Three cities were observed, i.e. Mataram, Bandung, and Surabaya. Ten road links were observedwhich consist of six 4 lanes-2 ways and four 6 lanes-2 ways divided roads. Surveys were carried out for 24 hours of a normal working day. Traffic counts were grouped every 15 minutes per direction, per lane for 3 vehicle types. i.e. light vehicle, heavy vehicle, and motorcycle. T-test of mean differences was used as a technique for analysis. The results show that the design lane was the most right lane and the values of C in Mataram, Bandung, and Surabaya were higher than those on the Manual.Keywords: vehicle distribution coeeficient, flexible pavement design